GAMBARAN ADIKSI MEDIA SOSIAL SISWA DI MASA PANDEMI COVID-19 - Ismi Nursina Putri; Euis Rohaeti; Devy Sekar Ayu Ningrum (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study was conducted with the aim of knowing the description of students who have social media addiction during the Covid-19 period at SMKN 1 Pacet, Cianjur Regency. This research was taken based on phenomena that occur in schools. According to Young, internet/social media addiction is defined as a person's inability to control himself in using the internet, resulting in a few problems that interfere with the performance of his brain. Students who have a fairly high social media addiction during the covid-19 pandemic. The method used in this study is a qualitative descriptive method. The data collection technique used in this research is to use interviews and observations that will produce data for this research. The sampling technique in this study used the purpouse sampling technique. The sample used was 10 students who had social media addiction during the Covid-19 pandemic. The results of this study are from the sample taken there are 5 students who have a high addiction to social media. This can be seen from the attitude of students who feel they cannot control themselves in accessing social media in online learning during the Covid-19 pandemic, this is due to the factors that influence students so that excessive social media addiction occurs. These factors are influenced by both internal and external factors.Keywords:Addiction, Social Media, Covid-19.